Practice on the herbal usage and associated factors among hypertensive patients at the Teaching hospital, Jaffna, Sri Lanka - Bandara, A.G.D.I.; Thuvaragan, S.; Guruparan, M.; Surenthirakumaran, R. (University of Jaffna, 2022)
Herbs are used in the complementary and alternative medicines and they are used by patients having non-communicable diseases such as hypertension. The objective of the study was to describe the practice of herbal usage and assess the associated factors on herbal usage among hypertensive patients attending the medical clinic at Teaching Hospital, Jaffna. It is a hospital-based cross-sectional analytical study conducted from November 2020 to October 2021. A systematic sampling method was used to select 427 hypertensive patients. The data were collected using a pre-tested and validated interviewer-administered questionnaire and data extraction form. Data were analysed using SPSS software. Chi-square test was used to assess the association between socio-economic and disease related factors and herbal usage. Mann-Whitney U test was used to assess the association between the knowledge on hypertension and practice of herbal usage. The response rate of patients was 99.52% (n=415). The mean age of patients was 53.73±8.33 years. The majority of the patients were female (65.5%, n=272) and completed secondary education only (47%, n=195). The prevalence of herbal usage among the hypertensive patients was 68% (n=282). Garlic, passion leaves, ginger, and polyherbal mixture were the most commonly used herbs among the patients. Three-fourths of the patients (76.2%) were consuming more than one herbs. The majority of the patients used herbs once in a week (39.7%) and for more than five years (46.8%). Also, most of the patients (59.2%) used herbs due to their uncontrolled blood pressure. Only 30.9% of patients disclosed their herbal usage to their physician. Among the socio-economic factors and other disease related factors, age (p=0.000), employment status (p=0.039), duration of hypertension (p=0.000), and family history of hypertension (p=0.000) had a significant association with herbal usage. Further, hypertension knowledge of patients (p=0.003) also was significantly associated with herbal usage. The majority of hypertension patients used herbs. Herbal usage is more prevalent among patients of older age, having hypertension for more than six years, having a family history of hypertension, patients with unemployment and self-works and patients having knowledge on hypertension. However, patients should disclose to physicians regarding their herbal usage for effective management of hypertension.
Keywords: Herbal usage; Hypertensive patients; Associated factor